Factors Related to Supportive Care Needs in Family Caregivers of Patients with Advanced Cancer - มหาวีรานนท์, อินทิรา; ธนศิลป์, สุรีพร; ฉิมหลวง, จรรยา (Journal of The Royal Thai Army Nurses, 2019)
The descriptive correlational research examined the supportive care needs and the relationship between selected factors related to supportive care needs in family caregivers of patients with advanced cancer. One hundred and eighty four participants was family caregivers of patients with advanced cancer were recruited by purposive sampling. Participants were family caregivers of the patients followed up at out-patient department of cancer clinics form 3 tertiary hospitals in Bangkok. The research instruments included the demographic data form and The State Anxiety Inventory form Y, The Social support assessment form, The Fatigue scale, The Edmonton Symptom Assessment Scale, The supportive care needs survey for partners and caregivers, The Knowledge assessment form and The Karnofsky Performance Status. Data were analyzed using mean, standard deviations and Pearson’s product moment Correlation. The research results were as follow: 1) The supportive care needs in family caregivers of cancer patients was at moderate level (mean = 3.09, SD = 0.74). 2) Social support and physical performance of patients were negatively and significantly related to supportive care needs in family caregivers of cancer patients (r = -.21 and -.22, p <.05 respectively) 3) Knowledge, anxiety, fatigue and symptoms severity were positively and significantly related to supportive care needs in family caregivers of cancer patients (r = .17, .20, .29 and .37, p <.05 respectively). However, age was not significantly related to supportive care needs in family caregivers of cancer patients (r = .06, p >.05)